AWARENESS ABOUT PRIMARY TEETH AND THEIR CARE AMONG GENERAL DENTISTS - A SURVEY - Yuvaraj, Samrithi; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Often the oral care of children is overlooked because of the fact that primary teeth are replaced by permanent dentition. Proper knowledge and awareness about primary dentition and its care among practicing dentists is essential in order to educate parents about the importance of oral care from a young age. The aim of this study is to assess the awareness about primary teeth and the care of primary teeth among general dentists. 100 dentists currently doing their internship in Chennai were surveyed using a multiple-choice questionnaire. Responses obtained were tabulated, and the results of the questionnaires were computed in percentages. 83% of the dentists surveyed said it was sufficient to brush once; 17% of the dentists surveyed felt it was essential to brush twice. 12% felt that chocolates were the chief cause of decay; 6% felt that prolonged bottle feeding predisposed children to caries; 7% felt that improper brushing technique could be the cause of decay; 75% of the dentists surveyed felt it was a combination of all the other factors that led to decay. This study found that the majority of dentists screened did have sufficient knowledge and awareness about the care and treatment of primary teeth. Any void in knowledge indicated by this study is a worrying concern and must be rectified by highlighting and stressing the importance of primary teeth during undergraduate education.